STUDY ON THE SEDIMENT TRANSPORT PROCESSES IN CAM RANH BAY USING MIKE 21/3 FM COUPLE MODEL - Tien, Nguyen Ngoc (Vietnam Journal of Marine Science and Technology, 2014)
In this paper, MIKE 21/3 FM COUPLE software was applied to assess the impact of wind, wave, current, tides in South-West monsoon on sediment transport and bottom terrain modification in Cam Ranh bay. The results show that: In South-West monsoon, the impact of wave and current is minor. Tide is dominant factor effecting sediment spread. In the flood tide phases, tide increases the penetration of sea water and sediment from open sea into the lagoons and vice versa during ebb tide phases, hence, sediment accumulation and bottom terrain modification is not much.